An investigation on the relationship between TQM and ICT in revenue agency organizations - Mahmoud Bani; Somayeh abdollahzadeh; Abolfazl Bani (Management Science Letters)
This paper presents an empirical investigation to study the effects of information and communication technology (ICT) on total quality management (TQM). The study is applied for a case study of revenue agency in city of Damghan, Iran. The proposed study consists of 33 questions in five categories including leadership and commitment of top management team, customer satisfaction, empowering employees and their partnership, organizational design perspective and quality of information system. Cronbach alpha has been calculated as 0.95, which validates the overall questionnaire. Using Pearson correlation ratio as well as t-student test, the study has determined that there was a positive and meaningful relationship between ICT and TQM components.